Tracking tumor evolution during the first-line treatment in brain glioma via serial profiling of cell-free tumor DNA from tumor in situ fluid - Sheng, Zhiyuan; Bu, Chaojie; Mei, Jie; Xu, Sensen; Zhang, Ziyue; Guo, Guangzhong; Gao, Yushuai; Xing, Liyuan; Chen, Zhongcan; Hernesniemi, Juha; Zemmar, Ajmal; Bu, Xingyao (Frontiers in Oncology, 2023)
Tumor in situ fluid (TISF) refers to the fluid within surgical cavities of glioma.Several studies preliminarily proved the value of cell-free tumor DNA (cf-tDNA) from TISF in the dynamic characterization of glioma genome. Here we assessed the potential utility of TISF cf-tDNA in a broad aspects of tumor evolution under therapeutic pressure.This study was conducted under an Institutional Review Board-approved protocol at Henan Provincial People's Hospital (China). Cf-tDNA samples were sequenced with a designed 68-gene panel. A total of 205 cf-tDNA samples from 107 patients were studied. Clinical relevance of serial cf-tDNA profiling during the postoperative course were analyzed.At least one tumor mutations were detected in 179/205 (87.3%) TISF cf-tDNA samples. Serial cf-tDNA was complementary of molecular residual disease and to initial tumors. Serial cf-tDNA revealed the selection of pre-existing mismatch repair-deficient cells by temozolomide as a resistant mechanism. cf-tDNA parameters during treatment were predictive of recurrence and serial cf-tDNA monitoring had diagnostic value for early recurrence. 223 potentially actionable genomic alterations were assessed in cf-tDNA samples, thereinto 78% not found in any tumor tissue.In conclusion, serial TISF cf-tDNA profiling is valuable in tracking tumor evolution of glioma during treatment and may be a feasible non-invasive option for monitoring of glioma in the future prospective studies and clinical practice.